2012
DOI: 10.1590/s0482-50042012000600008
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomiosite em adulto: experiência de um centro terciário brasileiro

Abstract: Objective: To report the results of a retrospective cohort involving 139 patients with dermatomyositis, conducted from 1991 to 2011. Methods: All patients met at least four of the fi ve Bohan and Peter criteria (1975). Results: The patients' mean age at disease onset was 41.7 ± 14.1 years, and mean disease duration was 7.2 ± 5.2 years. The sample comprised 90.2% white patients and 79.9% female patients. Constitutional symptoms occurred in less than half of the patients. Cutaneous and joint involvements occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
2
0
8
Order By: Relevance
“…Clinical manifestations include symmetrical muscle weakness of limbs and cutaneous lesions, including heliotrope rash and Gottron's papules. [1][2][3][4] Moreover, extra-skeletal manifestations can also occur such as joint, pulmonary, gastrointestinal and/or cardiorespiratory involvement. [2][3][4] Recent studies have shown a high prevalence of metabolic syndrome [5][6][7][8] and basal insulinemia 5,6 in systemic autoimmune myopathies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Clinical manifestations include symmetrical muscle weakness of limbs and cutaneous lesions, including heliotrope rash and Gottron's papules. [1][2][3][4] Moreover, extra-skeletal manifestations can also occur such as joint, pulmonary, gastrointestinal and/or cardiorespiratory involvement. [2][3][4] Recent studies have shown a high prevalence of metabolic syndrome [5][6][7][8] and basal insulinemia 5,6 in systemic autoimmune myopathies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] DM is an immune-mediated microangiopathy which affects both the skin and skeletal muscles diagnosed by confirming the presence of inflammatory infiltrate composed of B lymphocytes, macrophages and CD4+ lymphocytes, especially in the perivascular region of muscle tissue biopsy. [3][4][5]7 In the case of upper gastrointestinal tract involvement, patients with DM may be asymptomatic or present a variety of symptoms such as dysphagia, (dyspnea and computed tomography scan with evidence of interstitial lung disease and/or lung disease in "groundglass" abnormality), muscle strength of limbs (grade 0: no muscle contraction; grade I: trace of contraction; grade II: normal amplitude movements but incapable of countering the action of gravity; grade III: normal amplitude movements against gravity; grade IV: full mobility against gravity and degree of resistance; grade V: complete mobility against strong resistance against the action of gravity).…”
mentioning
confidence: 99%
“…A relação sexo feminino:masculino deste trabalho foi de 2,08:1. A raça majoritária foi a branca, assim como relatado em outros trabalhos (50,120), mas com distribuição de acordo com a população local, assim como mostrado em estudos (111,121).…”
Section: Discussionunclassified
“…O FAN é comumente encontrado em pacientes com MII, variando de 36 a 90% de positividade dos pacientes testados (7,50). O padrão pode ser nuclear ou citoplasmático, sendo este último relacionado às antissintetases.…”
Section: 1laboratóriounclassified